Comparative fatigue life estimations of Marine Propeller by using FSI. (February 2020) - Vijayanandh, R; Venkatesan, K; Senthil Kumar, M; Raj Kumar, G; Jagadeeshwaran, P.; Raj Kumar, R
Abstract: Generally, inward and outward effects are huge and prime in the rotating components. Based on the working environments of a rotor, the complexity is increased furthermore. In this work also deals the same problem, which is fatigue life estimation of marine propeller for different materials under given Ocean environments by using Ansys Fluent 16.2. The conceptual design of the Marine propeller is modelled with the help of CATIA. Fatigue life estimation on the rotor is key and complex output of this work, advanced methodology is mandatory for computation therefore Fluid-Solid Interaction (FSI) technique is used as advanced numerical simulation. Fluid properties such as density and operating pressure are used to define the Ocean environment in the Ansys Fluent 16.2. In the case of structural simulation, the existing materials such as Aluminium alloy and Stainless Steel are used for fatigue life estimation. Finally, the fatigue life estimation of marine propeller is extended for Composite material to compare the life of a rotor.